CARANSEBEŞ TOWN – SHORT LANDMARKS OF BANAT SPIRITUALITY - Daniel Aron Alic (Astra Salvensis, 2019)
Among Banat cities, Caransebeş comes into attention as a centre of Romanian culture and spirituality. Lived by Romanian people, the city and its neighbourhoods have passed through the vicissitudes of the history keeping pure the authentic of the area. Since the second half of the XIXth century, after the re-foundation of Caransebeş Diocese, national and cultural flag have been kept with care by the clergyman of the institution and the professor who contributed to the formation of the priests and teachers that, at their turn, contributed to the spread of religious feeling and alphabetization of the majority of Banat villages. In this town where also the most important personalities that contributed to the Great Union and later development of the province lived. All of these allows us to consider Caransebeş as the historical capital of Banat culture and spirituality.